PENINGKATAN PERKULIAHAN BAHASA INDONESIA UNTUK MEMBINA KETERAMPILAN MAHASISWA Abstract DALAM MENULIS KARYA ILMIAH - Zarnzani Zarnzani; Kastam Syamsi; Joko Santoso; Hartono Hartono (Jurnal Cakrawala Pendidikan, 2006)
icle is based on a classroom action research aimed at1I11"'1r"l11~ ....n'TO'fl~01n't in classes of Bahasa Indonesia at........... ,..,., ............, .... V ..... IIoJI'lIlo"_IJI,.V were VIJI,._~"'_.II.Jl.II.VLanguage A....Iu.'~"""'Q".4."AVJLA'"A....Iu.·~"""'''''... ''.a.V'A.a. Study Programs, numbering fifty-one,and thirty-eight, respectively. The analysis the__.11.'"'1-'.11..11. __ through observations, tests, and writing assignments, wasand qualitatively descriptive.o"'r.ln........\~111C"n1!4r'Ø't'\,. were based on the levelworks, which was indicated by the scores obtained.The resultsof the action research can be asfollows. First, the students' skills writing scientific works arecategorized good so that the learning model employed in theresearch, composedof discussion, assignment the form writingpractice, and lecture related to theoryof writing complete withwritten material of various forms, is considered good or appropriate.Second, an explorationof students' needs and a discussion to anagreement about the learning material, model, and evaluation haveimproved their awarenessof significant matters and theirresponsibilities in classes.